c - d; University of Dhaka. Institute of Modern languages (b, 2002)
Autobiographical reminiscences of a leftist leader, university teacher, and writer from Bangladesh about his involvement in political activities before the independence of his country in 1971.
In Bengali.
Keywords: Fazlul Karim, Sardar, -- 1925- -- Political activity; Political activists -- Bangladesh -- Biography; Communists -- Bangladesh -- Biography; Bangladesh -- Politics and government